2010
DOI: 10.1007/s10811-010-9557-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growth conditions on the cell dry weight per unit biovolume of Klebsormidium flaccidum (Charophyta), a typical ubiquitous soil alga

Abstract: The dry weight per unit biovolume of 810 single, living cells of the ubiquitous soil algae Klebsormidium flaccidum from 80 experiments were determined using a Mach-Zehnder double-beam interference microscope. Different substrates such as agarized nutrient solution, different soils, and slag heap material, different pH values, temperatures and light intensities were used and cells from both growth and stationary phase were measured. The total possible range of dry weight with respect to carbon per unit biovolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Unfortunately this is not the case. The dry matter content of cells varies greatly both within a population and between populations, not only for algae but for planktonic species in general [4] , and empirical calibration for each species is necessary to account for this.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately this is not the case. The dry matter content of cells varies greatly both within a population and between populations, not only for algae but for planktonic species in general [4] , and empirical calibration for each species is necessary to account for this.…”
Section: Resultsmentioning
confidence: 99%
“…These approaches use the measured particle diameter to automatically calculate the included wet biomass volume on the assumption that the particle is spherical. Conversion from buoyant mass or biovolume to dry weight is problematic, as the dry content of cells is highly variable both within and between populations [4] and so a constant average density cannot be assumed.…”
Section: Introductionmentioning
confidence: 99%
“…() developed a software‐aided analysis tool that allows image processing with precise measurements at a single pixel level. This improvement was indispensable for the development of MZM, allowing accurate quantification of dry masses at the single cell level, which is applicable to many biological systems (Jahnke et al ., ). Our study clearly shows that MZM has the potential to become a standard method for the analysis of the turgor pressure of fungal infection cells.…”
Section: Introductionmentioning
confidence: 97%
“…However, it is a convenient relative measure of cell count and commonly used for that purpose. Although some variation of the relationship between OD and DW can occur with differing temperature conditions (Jahnke, Mahlmann, Jacobs, & Priefer, 2011; Torzillo, Sacchi, & Materassi et al, 1991), such variations were generally minor in the experiments reported here and only occurred at the latter stages of growth at 35°C where the cultures displayed clear instabilities (declines) in pigmentation. Lower pigmentation, especially in the red spectral region, can lead to lower refractive indices at 750 nm, lower light scattering, and thus higher DW/OD ratios, as observed.…”
Section: Methodsmentioning
confidence: 62%